Queensland 1:10 000 series orthophoto map. 7963-413, Leadingham - Queensland. Department of Mapping and Surveying (Brisbane : Dept. of Mapping and Surveying, 1982)
Orthophoto map with contours at 5 metre intervals and spot.
Index to adjoining sheets.
Compilation date determined from aerial photography July 1978.
Keywords: Leadingham Creek Region (Qld.) -- Maps; Topographic maps; Remote-sensing maps